1971
DOI: 10.1104/pp.47.6.779
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of pH on the Products of Photosynthesis in 14CO2 by Chloroplast Preparations from Acetabularia mediterranea

Abstract: The effect of pH on the pathways of carbon in photosynthesis was examined in chloroplast preparations from Acetabularia mediterranea. The flow of carbon into a number of photosynthetic intermediates, particularly sucrose, glycine, serine, glycolate, and the insoluble fraction, was strongly influenced by pH. At higher pH a much larger portion of the SC entered intermediates of the glycolate pathway. Although maximal apparent photosynthesis occurred at pH 7.6 to 7.7, cytoplasmic pH was found to be 8.0 to 8.4, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…1), which is consistent with previous reports (5,11,12). Experiments of this kind, conducted at constant bicarbonate concentration, do not take into account the fact that the substrate for RuDP carboxylase is CO2 and not bicarbonate (4).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…1), which is consistent with previous reports (5,11,12). Experiments of this kind, conducted at constant bicarbonate concentration, do not take into account the fact that the substrate for RuDP carboxylase is CO2 and not bicarbonate (4).…”
Section: Resultssupporting
confidence: 89%
“…Another environmental parameter that may alter the relationship between photorespiration and photosynthesis is pH. In algae (11) and chloroplasts (5,12), it was concluded that photorespiration increased at high pH values because increasing the pH increased the rate of synthesis of glycolate. This conclusion was supported by experiments with RuDP carboxylase indicating that the pH optimum for oxygenation was higher than that for carboxylation (1,2 (14).…”
mentioning
confidence: 99%
“…The final reaction mixture volumes were 1 ml and contained 51. 4 ,ug Chl as well as 40 ,uCi of "14CO2." Total "CO2" and CO2 concentrations were identical to those identified in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…During photosynthesis under optimal conditions, i.e. saturating levels of CO2 in air, pH 8.5 in contrast to 7.5 increased glycolate yields in intact algal cells (4,11) and in algal as well as spinach chloroplasts (4,10). In all of these investigations, the effect of pH was monitored at only one concentration of CO2 and 02.…”
mentioning
confidence: 99%
“…(1) (2) (3) (4) The distribution of these inorganic carbon species is pHdependent as shown in Fig.1 Media pH is an important factor that could identify availability of inorganic carbon species for an aquatic photosynthetic organism and is one of crucial parameters influencing growth of algae [4][5][6][7][8][9][10][11][12]. According to Bano and Siddiqui, cyanobacterial species preferred to grow near neutral to alkaline pH and have growth optimum at near neutral [13][14].…”
Section: Introductionmentioning
confidence: 99%